2015 IEEE International Symposium on Technology and Society (ISTAS) 2015
DOI: 10.1109/istas.2015.7439421
|View full text |Cite
|
Sign up to set email alerts
|

"About your smartphone usage" — Privacy in location-based mobile participation

Abstract: Location-based mobile tools provide effective means for mobile participation, allowing better targeting of users and faster opinion gathering for municipalities and organizations. For participation purposes it is essential to reach the users as widely as possible, and for this, smartphones with ever-increasing adoption rates offer an optimal tool. However, privacy concerns might prevent the use of locationbased applications, which results in a bias in opiniongathering. In this paper, we present results of a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…People perform their own risk and benefit assessment when they face a choice. The benefits provided by mHealth apps can be free cost, convenience, real-time health services, saving time, and other monetary incentives [46,47]. If users believe that the benefits outweigh the security and privacy risks, they may choose to sacrifice privacy and enjoy the benefits offered by the service, even though they still have concerns.…”
Section: Discussionmentioning
confidence: 99%
“…People perform their own risk and benefit assessment when they face a choice. The benefits provided by mHealth apps can be free cost, convenience, real-time health services, saving time, and other monetary incentives [46,47]. If users believe that the benefits outweigh the security and privacy risks, they may choose to sacrifice privacy and enjoy the benefits offered by the service, even though they still have concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In this field of study, there are other proposed methods to conceal the location of a user [14] There are few existing studies regarding privacy perception surveys. in [18], results show that users have a variety of motivations for participating in location-based surveys and that these motivations depend on the type of the survey in question. This study concluded that users concerned with privacy are less likely to be motivated by a monetary benefit but by the importance of the topic and that the intrinsic motivators that drive the users concerned with privacy differ from those that drive unconcerned users.…”
Section: Related Workmentioning
confidence: 97%
“…Moreover, next-POI recommendation solutions have tried to address an important challenge of the domain, which is the lack of individual data about tourists' POI visits. In fact, tourists do have privacy concerns (Poikela et al 2015;Perentis, Vescovi, and Lepri 2015) and many tourists are reluctant to share their location with companies. As a consequence of that, for each single tourist, the set of opinions about the visited POIs., for example, booked hotels or attractions, could be very small and even empty (Bin et al 2019).…”
Section: Recommender Systems For Tourismmentioning
confidence: 99%
“…In fact, tourists do have privacy concerns (Poikela et al. 2015; Perentis, Vescovi, and Lepri 2015) and many tourists are reluctant to share their location with companies. As a consequence of that, for each single tourist, the set of opinions about the visited POIs., for example, booked hotels or attractions, could be very small and even empty (Bin et al.…”
Section: Recommender Systems For Tourismmentioning
confidence: 99%